Moral Value of Novel “Ayah Mengapa Aku Berbeda?” by Agnes Davonar - Marudut Bernadtua Simanjuntak; Siti Naharani Fauziah (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
The novel entitled “Ayah Mengapa Aku Berbeda?” is a novel that tells the story of Angel's life from childhood as a child with special needs. Angel's mother died while giving birth to Angel. His father patiently took care of Angel who was deaf since birth, sincerely made Angel like a normal child in general so that Angel would not feel discouraged. Her father's struggle so that Angel can attend public schools and get an education like children, in general, is not easy, because Angel has been rejected from several schools because Angel is deaf. This situation awakens Angel to always be grateful to God for everything he gets to form Angel into a person who is always grateful and does not give up easily. Novel “Ayah Mengapa Aku Berbeda?” Agnes Davonar's work has been successfully made into a film to educate every film audience to always be grateful for everything they have. This study uses qualitative methods, methods used to investigate, find, describe, and explain the quality or advantages of social influences that cannot be explained by a quantitative approach. This research is expected to have a positive impact on everyone who reads it and can implement it in life.